Developmental dynamics between reading and math in elementary school. Issue 1 (25th June 2020) - Erbeli, Florina; Shi, Qinxin; Campbell, Aaron R.; Hart, Sara A.; Woltering, Steven
Abstract: Reading and math attainment develop during elementary grades. Questions remain, though, about the co‐developmental nature of the relation between reading and math. This study examined dynamic, longitudinal pathways between reading and math in first through fourth grades. Participants of the study were 554 academically at‐risk children ( M age at the first assessment point = 6.57 years; SD  = 0.38) from Texas Project Achieve. Children were assessed utilizing the Woodcock‐Johnson–III reading and math measures. Results from dynamic bivariate latent change score models indicated unidirectional longitudinal coupling effects from reading to math. Specifically, average and high levels of reading performance were associated with subsequent gains in math growth, in particular for below average performing children in math. In contrast, low levels of reading performance had negligible or no amplifying influences on change in math growth. The nature of the dynamics was replicated even when controlling for nonverbal cognitive abilities. Results demonstrated that good reading skills pave the way for children to develop their math skills. Such findings underscore the importance of considering reading performance in treating math difficulties. Abstract : The main finding was that reading performance influenced change in math gains in subsequent grades rather than vice versa. This was particularly true for those children who were good readers. In poor readers, no amplifying effects from reading to math were detected.